Isolation of bacteria prospective for obtaining organomineral biomineral fertilization from waste water sediments (Experimental biology, 2021)
Biological preparations are modern and effective means for processing waste, as a result of the use of which it is possible to obtain high-quality organic fertilizers rich in nitrogen compounds, which do not contain pathogenic microflora and helminth larvae. In recent years, many problems have arisen around the sewage treatment facilities in the country with the disposal of sludge in sludge maps. The method of biological fermentation and utilization using active strains of microorganisms is proposed as an effective solution to this issue.The article presents the results of studies on the isolation of bacteria from sewage sludge, promising for the production of organic-mineral biofertilizer, the study of their enzymatic activity and the ability to utilize sludge. Sludge samples were taken from treatment facilities in Nur-Sultan city and Rudny town. Six active strains were isolated: Bacillus mojavensis, Bacillus fusiformis, Bacillus amyloliquefaciens, Pseudomonas lundensis, Enterobacter sp. and Ochrobactrum sp. Bacteria were identified by 16S rRNA method.The results of laboratory experiments on the disposal of sludge from municipal wastewater have shown that the bacteria Enterobacter sp. and Ochrobactrum sp. have the highest activity. Sludge utilization in model experiments was observed up to 70%. The association of three bacterial strains of the genus Bacillus was less efficient in the process of sludge utilization compared to monocultures of Enterobacter sp. and Ochrobactrum sp. In general, the experiments have shown the promise of using microbial biomass for the disposal of sludge from urban wastewater. Prospective strains include Enterobacter sp. and Ochrobactrum sp. with 47% and 69% of sludge utilization, respectively.
Keywords: шлам, тыңайтқыштар, микроорганизмдер, қалдықтар, өңдеу, кәдеге жарату